1992
DOI: 10.1007/bf01647650
|View full text |Cite
|
Sign up to set email alerts
|

Stoma anxieties: A comparison of the attitudes of Asian migrants and the indigenous population in the United Kingdom towards abdominal surgery and the role of intestinal stomas

Abstract: We have studied stoma care nurses' experience with Asian patients having a stoma. The general public's attitudes to abdominal surgery in general were assessed in a survey of employees in Leicester. Many stoma care nurses are aware of the needs of Asian patients, especially with regards to ethnic dress, but only half of the ostomists who wanted to see a stoma care nurse or fellow ostomist were able to do so (chi 2 = 4.5, p less than 0.03). All ostomists considered counselling on education, employment and marria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…Ostomists have numerous concerns to address including fear of stool leakage, odour, wearing a pouch, changing the pouch and change in body appearance 37 . These concerns have proven to be similar across different cultures 38 . Our local patients face similar challenges, made more acute by the emergent nature of the first stage surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ostomists have numerous concerns to address including fear of stool leakage, odour, wearing a pouch, changing the pouch and change in body appearance 37 . These concerns have proven to be similar across different cultures 38 . Our local patients face similar challenges, made more acute by the emergent nature of the first stage surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kennedy et al [7] found that psychological problems as sociated with sexual activity were not unusual following an ileostomy. Long-term follow-up by stoma nurses could detect and perhaps alleviate their difficulties, although recent work would cast doubt on this assumption [16].…”
Section: Discussionmentioning
confidence: 99%
“…Further support comes from the experience of ostomists during the 1990s when an understanding of issues related to siting the stoma and the sari line were expressed together with difficulties in accessing specialist advice. 19 This study would suggest that we need to radically review the way in which we deliver care to patients with inflammatory bowel disease from minority communities. Quality of care is defined in terms of clientcentred services, meeting needs and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Further support comes from the experience of ostomists during the 1990s when an understanding of issues related to siting the stoma and the sari line were expressed together with difficulties in accessing specialist advice. 19…”
Section: Discussionmentioning
confidence: 99%